Sistem Informasi Pemesanan Produk Teh Menggunakan Midtrans Payment Gateway Berbasis Android - Haerani, Sintia; Fakhriza, M. (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The development of technology today is very rapid, thus encouraging people to use technology more developed. Nowadays, marketing systems and product promotion via the internet are experiencing rapid growth. Many companies use information technology as a corporate strategy to provide products to all consumers without limiting space and time. marketing of tea products carried out by PTPN IV is less efficient because it is only distributed in supermarkets and minimarkets. the lack of marketing to the public such as shop owners or wholesalers makes it difficult for consumers to reach these tea products, especially consumers who are far from supermarkets or minimarkets. by building a tea product ordering information system integrated with midtrans payment gateway. With the construction of this system consumers can make purchases directly to the center and can make direct payments with the payment methods provided by midtrans. this system can minimize existing problems related to ordering and marketing. This system allows the admin to easily manage marketing and ordering data. For consumers (users) can better maintain the security of order data.